A new species of Eutrombicula Ewing, 1938 (Trombidiformes: Trombiculidae) from the Galápagos Islands, with a checklist of Ecuadorian chiggers - Bassini-Silva, Ricardo [UNESP]; Welbourn, Cal; Ochoa, Ron; Barros-Battesti, Darci Moraes [UNESP]; de Castro Jacinavicius, Fernando (Springer Nature, 2023)
Few studies have been carried out on the Ecuadorian chigger fauna. In this study, we are describing a new species of Eutrombicula from the Galápagos Islands. Also, we provide an updated checklist of Ecuadorian and Galápagos Islands chiggers, including a new host association and locality record for Eutrombicula nerudai Stekolnikov and González-Acuña.